5G Coupler Design for Intelligent Transportation System (ITS) Application - Dyg Norkhairunnisa Abang Zaidel; Norhudah Seman; Mohd Ridhuan Mohd Sharip; Dyg Azra Awang Mat; Nur Alia Athirah Mohtadzar (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Aiming to achieve 3-dB coupling, operating in fifth generation (5G) technologies, this paper introduces a new design of tight coupling coupler that will be operated in 5G technologies. Two stubs and two slots have been implemented into the 3-dB coupler design in order to achieve impedance matching between the ports and to give better coupling performances, respectively. Moreover, a study on the stubs’ and slots’ effects towards the S31 of the 3-dB coupler has also been presented in this paper. The proposed coupler is designed on Rogers RO4003C substrate. The simulation results and the analytical study on the stubs and slots implementation show that both stubs and slots affect the performance of the coupling coefficient.